Numerical investigation of novel prefabricated hollow concrete blocks for stepped-type seawall structures. (1st November 2019) - Dang, Bao-Loi; Nguyen-Ngoc, Hau; Hoang, Thao Duc; Nguyen-Xuan, H.; Abdel Wahab, Magd
Highlights: Three dimensional (3D) numerical model for seawall structures is developed. Load-bearing capacity of hollow block and the stability of seawall structures. Soil-structure interaction between blocks and soil is taken into account in the numerical model. Elastic settlement of foundation is evaluated and can be considered for design of coastal structures. Abstract: In this paper, a novel Three-Dimensional (3D) prefabricated Hollow Concrete Block (HCB), which can form seawall structures, is numerically investigated. Unlike the traditional gravity-type seawalls, this is a lightweight structure in comparison with the conventional ones, but it possesses advantageous features under complex loading conditions. The load bearing capacity of HCB itself under the wave loading has been examined. The highly complicated soil-structure interaction is taken into account so that the underlying simulation may predict realistic behaviors of seawall structures. The results indicate that this novel seawall model requires fewer concrete materials, but is adequate under sea wave attacks. For instance, stresses induced on seawall blocks are smaller than the allowed stresses of concrete. By adding sand into the HCB components to increase its weight and using supported-piles system, the stability of the seawall structure is enhanced and its settlement is reduced. The results obtained are evaluated using reference studies, from literature, regarding the elastic settlement of foundation. The techniques proposed in this paper, therefore, may provide an important pathway for further studies aiming to achieve optimal and reliable coastal designs taking into account the impacts of climate change.